Behind the Scenes of Successful Research in Emergency Medicine: Nine Tips for Junior Investigators. (12th September 2019) - Probst, Marc A.; Caputo, Nicholas D.; Chang, Bernard P.
Narrative Abstract: Education related to clinical research often focuses on methodology, statistics, ethics, and study design. While knowledge of these conventional skills is essential to the operationalization of research, many "soft" skills related to leadership, communication, and team management are critical to the successful conduct research in the real world. Conducting clinical research in the emergency department is generally a challenging endeavor. Based on our prior experience as clinical researchers and a narrative review of the published literature, we offer nine practical strategies to help junior investigators conduct research. To successfully execute a research study, investigators must know how to motivate their team, create a brand around their study, communicate effectively, maximize clinician and patient engagement, and celebrate victory, among other skills. These skills and strategies are often missing from the formal research education and in peer‐reviewed manuscripts but are, in fact, invaluable to the successful development of junior investigators. Thus, we offer the "story behind the study" in an effort to contribute to research education with material that is not typically covered in formal curricula.